Molecular characterization of diaporthe citri isolates using faflp technique. - Nozaki, Márcia de Holanda [UNESP]; Camargo, Margarete [UNESP]; Lemos, Eliana Gertrudes Macedo [UNESP]; Aukar, Ana Paula de Andrade [UNESP]; Barreto, Modesto [UNESP] (My University, 2006)
Citriculture is a market in expansion specially in Sao Paulo State, whose importance in the economy is already recognized. Like any other cultivated species, the increase of planted areas contributes to an increase in disease problems. Thus, many diseases affect citrus species, including melanose, caused by Diaporthe citri (Wolf.), to which most commercial varieties are susceptible to the disease. Kno-wledge of the intra-specific diversity is important when selecting varieties for resistance. This study evaluated the genetic variability among Diaporthe citri isolates, obtained from different geographical regions, varieties, and parts of the plant using molecular markers. Amplified Fragment Length Polymorphism (AFLP) markers were used to characterize ten isolates of this pathogen. Genomic DNAs extracted from mycelial mass were used in amplification reactions. fAFLP allowed separation of the isolates into four distinct groups. However, genetic similarity analysis did not group isolates by locati-on, variety or part of the plant.
Caracterização molecular através da técnica faflp de isolados de diaporthe citri
Keywords: Citrus; Genetic variability; Melanose; Polymorphism